Analysis of The Integrity of Attitudes, Behavior, Openness and Honesty of Captured Fisheries Enterprises for The Conservation of Fish and Marine Resources - Noordin, Rumaizah Mohd; Istiqomah, Titis; Ferdian, Muh. Agus; Farida, Siti (Politeknik Kelautan dan Perikanan Karawang, 2024)
Integrity of attitude, behavior, openness and honesty are important things that capture fisheries business actors must have. Deviations in integrity are allegedly equivalent to criminal acts of corruption because they have the potential to cause very large losses to the state, which are difficult to detect and the value of the losses. In addition, failure to fulfill integrity has a huge potential for loss of sustainability of fisheries resources in the long term, and is difficult to recover. The research aims to examine the relationship between the integrity of capture fisheries business actors and efforts to preserve fish and marine resources. Descriptive research using a literature study approach combined with a limited discussion process with aquatic resource management experts in order tomaintain the sustainability of fish population dynamics due to capture fisheries exploration. The research results show that the integrity component which concerns attitudes, behavior, openness and honesty of capture fisheries business actors is an absolute thing that must be implemented and developed. Potential state losses worth billions of rupiah accompanied by massive damage to marine resources can be avoided if capture fisheries business actors carry out exploration properly and report their activities honestly and openly to the competent government authorities as a control over resource sustainability.